Assessing Halal logistics competence: An Islamic-based and resource-based view - Karia, N. (Institute of Electrical and Electronics Engineers Inc., 2015)
Halal logistics is an innovation of delivering of Halal products or service. It is newly emerging area in the logistics industry due to Halal global dynamic business architecture. Global Halal market is indeed enormous due to tremendous growth of global Halal demand from Muslims and non-Muslim consumers. According to theory the growth of Halal industry and Halal market enhance the demand for Halal logistics. However, to date only few third-party logistics (3PL) firms are certified by Halal certification, indicating not many 3PLs involved in Halal logistics. Hence the successful implementation of Halal logistics operations is yet to be seen and the mechanism of Halal logistics competence is still in the 'black-box'. To unfold these crucial gaps, this article applies Islamic-based approach enshrined in Al-Quran and Hadith to explore the basic determinants of Halal services and Halal logistics services in particular and further identify prominence determinants of Halal logistics competence in delivery Halal products and service by Malaysian 3PL firms. Â© 2015 IEEE.